PENAFSIRAN TINDAK PIDANA PENODAAN AGAMA DALAM PERSPEKTIF HUKUM - Kurnia Dewi Anggraeny (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2017)
This paper examines the interpretation of the crime of religious blasphemy as defined by grammatical interpretation and meaning in Indonesian positive law. Background case of religious defamation by Basuki Tjahaja Purnama or Ahok. with the decision of No.1537Pid.B / 2016 / PN. Jkt Utr. In that case there is a phrase "Be lied to use Al-Maidah letters" mentioned Ahok in front of citizens with the context of choosing leaders according to Islam in a working visit to the Thousand Islands on 27 September 2016. The word lied is an instrument that is not neutral because the word is lied to, humbled when juxtaposed with the word of the Quran. The author uses normative juridical methods in searching for the meaning of religious defamation through the perspective of Indonesian positive law and the opinions of some Muslim jurists and scholars. Law No.1 / PNPS / Year 1965 is used as the basis and guidance in handling the issue of the Crime of Blasphemy in Indonesia, while Article 156 and Article 156 a of the Criminal Code are copies of Law No.1 / PNPS / Year 1965 which is the source in the verdict in every decision in case of defamation of religion in Indonesia. The formulation of the crime itself does not contain a clear explanation and interpretation of deeds classified as defamation of religion, so that the formulation of religious defamation rules is needed to narrow the space of interpretation in the draft Penal Code (R-KUHP). Keywords: Interpretation, Blasphemy, Legal Perspective